Secondary growth as a determinant of plant shape and form - Ragni, Laura; Greb, Thomas (Seminars in cell & developmental biology, 2018)
Plants are the primary producers of biomass on earth. As an almost stereotypic feature, higher plants generate continuously growing bodies mediated by the activity of different groups of stem cells, the meristems. Shoot and root thickening is one of the fundamental growth processes determining form and function of these bodies. Mediated by a group of cylindrical meristems located below organ surfaces, vascular and protective tissues are continuously generated in a highly plastic manner, a competence essential for the survival in an ever changing environment. Acknowledging the fundamental role of this process, which is overall designated as secondary growth, we discuss in this review our current knowledge about the evolution and molecular regulation of the vascular cambium. The cambium is the meristem responsible for the formation of wood and bast, the two types of vascular tissues important for long-distance transport of water and assimilates, respectively. Although regulatory patterns are only beginning to emerge, we show that cambium activity represents a highly rewarding model for studying cell fate decisions, tissue patterning and differentiation, which has experienced an outstanding phylogenetic diversification.